A Reclamation Scheme For Sulphidic Waste Rock At Stratoni Mines, Greece - G. Gaidajis (Society for Mining, Metallurgy & Exploration, 2002)
For the environmentally safe management of the sulphidic waste rock produced from the Stratoni mining facilities, TVX Hellas has examined, within the frame of the funded European research program ROLCOSMOS, the effectiveness of an alternative rehabilitation scheme involving the segregation of the sulphide rich components of waste rock and the engineered application of alkaline additives. The examined waste rock management scheme was evaluated with laboratory test work followed by pilot-scale field applications. In this paper, the results from the two-year monitoring period of the pilot scale application are presented.